Satisfação e a lealdade ao destino na perspetiva do mercado britânico no Algarve - Café, Telma Pacheco (2023)
This research approaches the British market that visits the Algarve region. In specific, this research aimed to characterize the British market regarding the following dimensions: socio-demographic profile, description of the visit, satisfaction with the tourist experience and destination loyalty. In order to withstand those main aims, this study used data from the project SAICT-ALG/39588/2018 (TurExperience - Tourist experiences' impacts on the destination images: searching for new opportunities to the Algarve). For the data collection, a questionnaire survey, including 32 questions, was applied. A total of 465 British tourists were surveyed. Data were collected during the high season of the tourism activity of 2021, between July and September. The results contribute to the literature on the impacts of tourism on satisfaction and loyalty in the British market. In this context, the results indicate that British tourists are satisfied with the region and pretend to return a day later. These results can assist tourism companies and public decision-makers in identifying actions and policies that can foster the tourism sector regarding this important market.